Ergonomic design of CNC milling machine for safe working posture - Isa , Halim; Ab. Rahman, Mahmood; Hasan, Hazmilah; Haeryip , Sihombing; Adi , Saptari; Baharudin, Abu Bakar (Trans Tech Publications, 2014)
In milling operation, Computer Numerical Control (CNC) milling machine has been recognized as one of effective solutions for high productivity, efficiency, and precision. However, the existing CNC milling machine has contributed to ergonomics-related problems such as awkward working posture. The aim of this study is to redesign the existing CNC milling machine by considering working posture of the machinist. This study performed questionnaire survey to determine ergonomics feature requirements from the machinist. The requirements of the machinist are then translated using Quality Function Deployment (QFD) to obtain technical specifications of new design CNC milling machine. The working posture of machinist during operating the existing CNC milling machine and the redesigned CNC milling machine was assessed using Rapid Upper Limb Assessment (RULA). Based on the analysis, the redesigned CNC milling machine has improved the working posture as shown by low score of RULA. This study concluded that by considering the ergonomics feature requirements to the design of CNC milling machine enabled the machinists to perform milling operation in safe working posture. This study suggests that environmental factors should be considered in the future research works.